The Presence of the Private Sector in Criminal Justice Enforcement and Its Comparative Study in the Criminal Laws of Iran and the USA - Mohseny, Farid; Jalilzadeh, Morteza (Journal of History Culture and Art Research, 2017)
From 1980 onwards, the privatization under the influence of the neoliberal politics supremacy in the world entered the criminal justice arena as well. In that year, the government and the private sector entered into conventions that mandated the collaboration of the private sector in the process of punishment and to undertake the criminal justice services. The political groups which agreed with the privatization at national levels started to expand the privatization as they came to power and the criminal justice apparatus was no exception to the rule. A higher incarceration rate was an inevitable outcome of the increase in the severity of the punishment and the increasing number of violations that carried a prison sentence. In the field of penalty enforcement, the private companies can build jails very rapidly and cheaply. The presence of the private sector in the implementation of criminal justice from the viewpoint of Iran’s law can be investigated from two perspectives. First, in terms of religious jurisprudence approach to the subject and second, from the viewpoint of the relevant rights.